An Optimized Third-Harmonic Injection Reduces DC-Link Voltage Ripple in Cascaded H-Bridge Converters up to 50% for all Power Factors - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (2023 25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe))
Star-connected cascaded H-bridge Converters require large DC-link capacitors to buffer the second-order harmonic voltage ripple. First, it is analytically proven that the DC-link voltage ripple is proportional to the apparent converter power and does not depend on the power factor for nominal operation with sinusoidal reference arm voltages and currents. A third-harmonic zero-sequence voltage injection with an optimal amplitude and phase angle transforms the 2nd harmonic to a 4th harmonic DC-link voltage ripple. This reduces the voltage ripple by exactly 50% for all power factors at steady-state at balanced conditions. However, this requires 54% additional modules for unity power factor operation and even 100% for pure reactive power operation to account for the increased reference arm voltages due to the large amplitude of the optimal third-harmonic injection. If not enough modules are available, an adaptive discontinuous PWM is utilized to still minimize the voltage ripple for the given number of modules and power factor. With a very limited number of modules (modulation index is 1.15), the proposed method still reduces the DC-link voltage ripple by 24.4% for unity power factor operation. It requires the same number of modules as the commonly utilized 3rd harmonic injection with 1/6 of the grid voltage amplitude and achieves superior results. Simulations of a 10 kV/1 MVA system confirm the analysis.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Capacitor voltage ripple; Zero sequence voltage; Third harmonic injection

Influence of cutting clearance and punch geometry on the stress state in small punch test - Otroshi, Mortaza; Meschut, Gerson (Engineering Failure Analysis)
The presented paper aims to characterize the damage and fracture behavior of HX340LAD Micro-Alloyed steels using small punch test. Variations with respect to punch geometries and cutting clearance are made to describe the damage behavior of the material under different loading conditions. Experimental investigations are conducted to identify the crack initiation in the specimens. Furthermore, the numerical FEM simulations are performed to identify the stress state at crack initiation. It is shown that different stress states from shear to biaxial tension can be achieved by changing the geometries of punch and varying the cutting clearance. Moreover, it is presented how changing the configurations can influence the stress state variables: Triaxiality and lode angle parameter.
Keywords: Ductile damage; stress state; small punch test; triaxiality; lode angle parameter

Zero-Sequence Voltage Reduces DC-Link Capacitor Demand in Cascaded H-Bridge Converters for Large-Scale Electrolyzers by 40% - Unruh, Roland; Schafmeister, Frank; Böcker, Joachim (24th European Conference on Power Electronics and Applications (EPE'22 ECCE Europe))
Cascaded H-bridge Converters (CHBs) are a promising solution in converting power from a three-phase medium voltage of 6.6 kV...30 kV to a lower DC-voltage in the range of 100 V...1 kV to provide pure DC power to applications such as electrolyzers for hydrogen generation, data centers with a DC power distribution and DC microgrids. CHBs can be interpreted as modular multilevel converters with an isolated DC-DC output stage per module, require a large DC-link capacitor for each module to handle the second harmonic voltage ripple caused by the fluctuating input power within a fundamental grid period. Without a zero-sequence voltage injection, star-connected CHBs are operated with approximately sinusoidal arm voltages and currents. The floating star point potential enables to utilize different zero-sequence voltage injection techniques such as a third-harmonic injection with 1/6 of the grid voltage amplitude or a Min-Max voltage injection. Both well-known methods have the advantage to reduce the peak arm voltage and thereby the number of required modules by 13.4 % (to √ 3 2). This paper proves analytically that the third-harmonic injection with 1/6 of the grid voltage amplitude reduces the second harmonic voltage ripple by only 15.1 % compared to no-voltage injection for unity power factor operation and balanced grid voltages. Then it is shown, that the Min-Max injection has the often overlooked advantage of reducing the second harmonic voltage ripple by even 18.8 %. By applying the here proposed zero-sequence voltage injection in saturation modulation, the second harmonic voltage ripple of the DC-link capacitors is reduced by even 24.3 %, while still requiring the same number of modules as the Min-Max injection. For a realistic number of reserve modules, the overall energy ripple in the DC-link capacitors is reduced by 40 %.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Zero sequence voltage; Third harmonic injection; Capacitor voltage ripple

Adaptive Zero-Sequence Voltage Injection for Modular Solid-State Transformer to Compensate for Asymmetrical Fault Conditions - Unruh, Roland; Lange, Jarren; Schafmeister, Frank; Böcker, Joachim (23rd European Conference on Power Electronics and Applications (EPE'21 ECCE Europe))
Modular solid-state transformers (SSTs) are a promising technology in converting power from a 10kV three-phase medium voltage to a lower DC-voltage in the range of 100…400V to provide pure DC power to applications such as electrolyzers for hydrogen generation, data centers with a DC power distribution and DC micro grids. Modular SSTs which can be interpreted as modular multilevel converters with an isolated DC-DC output stage per module, are designed with redundant modules to increase reliability. Usually, each of the three arms operates independently, and therefore, only a fixed number of faulty modules can be compensated in each arm, even if all modules are operational in the remaining two arms. With the proposed zero-sequence voltage injection, up to 100% more faulty modules can be compensated in an arm by employing the same hardware. In addition, module power imbalances are nearly eliminated by utilizing a fundamental frequency zero-sequence voltage. A dominant 3rd harmonic zero-sequence voltage injection in combination with the 5th, 7th and several higher order harmonics with adaptive (small) amplitudes minimize the required arm voltages at steady-state. For nominal operation or symmetrical faults, the proposed technique is equivalent to the well known Min-Max voltage injection, which already reduces the peak arm voltage by 13.4% compared to a constant star point potential. A statistical analysis proves, that the expected number of tolerable faulty modules of the 1MW SST increases by 12% without the need for additional hardware.
Keywords: Solid-State Transformer; Zero sequence voltage; Fault handling strategy; Power balance control technique; Three-phase system

Regulating Transitions from School to Work. An Institutional Ethnography of Activation Work in Action - Dahmen, Stephan
How are activation programs for the young unemployed implemented? How do street-level bureaucrats deal with competing rationalities and demands for action? Transition policies increasingly aim at promoting self-regulation and constructing employable subjects. Stephan Dahmen explores the practical regulation of biographical transitions in activation programs for the young unemployed by focusing on the interactive accomplishment of activation work. The study reveals how the critical tensions of activation policies are continually re-interpreted and adapted to local contingencies and describes the various organisational technologies used for creating employable subjects.
Keywords: Youth; Welfare State; Transitions; Human Service Organizations; Institutional Ethnography; Activation; Sociology of Conventions; Work; Education; Educational Research; Sociology of Education; Social Pedagogy; History of Education; Bielefeld University Press

Regulating Transitions from School to Work. An Institutional Ethnography of Activation Work in Action - Dahmen, Stephan
How are activation programs for the young unemployed implemented? How do street-level bureaucrats deal with competing rationalities and demands for action? Transition policies increasingly aim at promoting self-regulation and constructing employable subjects. Stephan Dahmen explores the practical regulation of biographical transitions in activation programs for the young unemployed by focusing on the interactive accomplishment of activation work. The study reveals how the critical tensions of activation policies are continually re-interpreted and adapted to local contingencies and describes the various organisational technologies used for creating employable subjects.
Keywords: Youth; Welfare State; Transitions; Human Service Organizations; Institutional Ethnography; Activation; Sociology of Conventions; Work; Education; Educational Research; Sociology of Education; Social Pedagogy; History of Education; Bielefeld University Press

Online State Estimation for Microscopic Traffic Simulations using Multiple Data Sources* - Malena, Kevin; Link, Christopher; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (VEHITS 2021 Proceedings of the 7th International Conference on Vehicle Technology and Intelligent Transport Systems)
The online fitting of a microscopic traffic simulation model to reconstruct the current state of a real traffic area can be challenging depending on the provided data. This paper presents a novel method based on limited data from sensors positioned at specific locations and guarantees a general accordance of reality and simulation in terms of multimodal road traffic counts and vehicle speeds. In these considerations, the actual purpose of research is of particular importance. Here, the research aims at improving the traffic flow by controlling the Traffic Light Systems (TLS) of the examined area which is why the current traffic state and the route choices of individual road users are the matter of interest. An integer optimization problem is derived to fit the current simulation to the latest field measurements. The concept can be transferred to any road traffic network and results in an observation of the current multimodal traffic state matching at the given sensor position. First case studies show promosing results in terms of deviations between reality and simulation.
Keywords: Microscopic Traffic Simulation; Online State Estimation; Mixed Road Users; Sensor Fusion; Integer Programming; Route Choice; Vehicle2Infrastructure

1-MW Full-Bridge MMC for High-Current Low-Voltage (100V-400V) DC-Applications - Unruh, Roland; Schafmeister, Frank; Fröhleke, Norbert; Böcker, Joachim (PCIM Europe digital days 2020; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)
A full-bridge modular multilevel converter (MMC) is compared to a half-bridge-based MMC for high-current low-voltage DC-applications such as electrolysis, arc welding or datacenters with DC-power distribution. Usually, modular multilevel converters are used in high-voltage DC-applications (HVDC) in the multiple kV-range, but to meet the needs of a high-current demand at low output voltage levels, the modular converter concept requires adaptations. In the proposed concept, the MMC is used to step-down the three-phase medium-voltage of 10 kV. Therefore, each module is extended by an LLC resonant converter to adapt to the specific electrolyzers DC-voltage range of 142-220V and to provide galvanic isolation. The proposed MMC converter with full-bridge modules uses half the number of modules compared to a half-bridge-based MMC while reducing the voltage ripple by 78% and capacitor losses by 64% by rearranging the same components to ensure identical costs and volume. For additional reliability, a new robust algorithm for balancing conduction losses during the bypass phase is presented.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Capacitor voltage ripple; Zero sequence voltage; Full-Bridge

Ground State Connectivity of Local Hamiltonians - Gharibian, Sevag; Sikora, Jamie (ACM Transactions on Computation Theory (TOCT))
Keywords: Local Hamiltonian; ground state connectivity; quantum Hamiltonian complexity; reconfiguration problem

Using the turbo principle for exploiting temporal and spectral correlations in speech presence probability estimation - Vu, Dang Hai Tran; Haeb-Umbach, Reinhold (38th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2013))
In this paper we present a speech presence probability (SPP) estimation algorithmwhich exploits both temporal and spectral correlations of speech. To this end, the SPP estimation is formulated as the posterior probability estimation of the states of a two-dimensional (2D) Hidden Markov Model (HMM). We derive an iterative algorithm to decode the 2D-HMM which is based on the turbo principle. The experimental results show that indeed the SPP estimates improve from iteration to iteration, and further clearly outperform another state-of-the-art SPP estimation algorithm.
Keywords: correlation methods; estimation theory; hidden Markov models; iterative methods; probability; spectral analysis; speech processing; 2D HMM; SPP estimates; iterative algorithm; posterior probability estimation; spectral correlation; speech presence probability estimation; state-of-the-art SPP estimation algorithm; temporal correlation; turbo principle; two-dimensional hidden Markov model; Correlation; Decoding; Estimation; Iterative decoding; Noise; Speech; Vectors